2012
DOI: 10.1016/j.apunts.2011.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Incidencia lesional en el fútbol profesional español a lo largo de una temporada: días de baja por lesión

Abstract: El fút bol cons ti tu ye en nues tro país, al igual que en otros Esta dos de nues tro en tor no, un fe nó me no que tras cien de de lo me ra men te de por ti vo para con ver tir se en un re fe ren te so cial que des pier ta pa sio nes y que tie ne su con si guien te re fle jo en los me dios de co muni ca ción so cial. No es pues de ex tra ñar que de for ma diaria la pren sa de por ti va de ám bi to na cional pro por cio ne in for ma ción cons tan te so bre la ma te ria, in clu yen do lo con cernien te a las le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 29 publications
1
13
0
12
Order By: Relevance
“…Studies on professional soccer have also found that 17-22 year old age groups sustained fewer hamstring strains than the older soccer players (Woods et al, 2004). The dominant leg accounts for a greater frequency of lesions -54.4% vs 36.5% in the non-dominant leg (Noya, 2015), but no significant differences were observed in the number of hamstring injuries between the dominant and the non-dominant leg (Freckleton & Pizzari, 2013). Men were 64% more likely to sustain a hamstring strain injury than women (Cross, Gurka, Saliba, Conaway, & Hertel, 2013) and they had a higher rate of re-injury as well (22% vs 12%) (Cross et al, 2013).…”
Section: Risk Factorsmentioning
confidence: 95%
See 4 more Smart Citations
“…Studies on professional soccer have also found that 17-22 year old age groups sustained fewer hamstring strains than the older soccer players (Woods et al, 2004). The dominant leg accounts for a greater frequency of lesions -54.4% vs 36.5% in the non-dominant leg (Noya, 2015), but no significant differences were observed in the number of hamstring injuries between the dominant and the non-dominant leg (Freckleton & Pizzari, 2013). Men were 64% more likely to sustain a hamstring strain injury than women (Cross, Gurka, Saliba, Conaway, & Hertel, 2013) and they had a higher rate of re-injury as well (22% vs 12%) (Cross et al, 2013).…”
Section: Risk Factorsmentioning
confidence: 95%
“…In the Spanish football, muscle injuries accounted for 49.1% of all the injuries in professional clubs (Noya, 2015). The thigh was the most prevalent site for injury, with 81% of thigh injuries in English soccer players classified as muscular strains.…”
Section: Injuries In Soccermentioning
confidence: 99%
See 3 more Smart Citations